The interaction between microbiome and host central nervous system: the gut-brain axis as a potential new therapeutic target in the treatment of obesity and cardiometabolic disease. (2nd July 2020) - Wijdeveld, Madelief; Nieuwdorp, Max; IJzerman, Richard
ABSTRACT: Introduction: The role of the intestinal microbiota in host cardiometabolic health and disease has gained significant attention over recent decades. Previous studies have shown effects on metabolic health through gut microbiota modulation; this suggests diverse interaction pathways that constitute the communication between gut microbiota and host central nervous system, the so-called gut-brain axis. Areas covered: This article provides an overview of the various mechanisms that may mediate the gut-brain axis. It places an emphasis on cardiometabolic health, including effects of short-chain fatty acids (SCFA), alterations in neurotransmitters and gut peptides and microbial effects on chronic inflammation and immune function. Moreover, this paper sheds light on whether these mechanisms afford therapeutic targets to promote metabolic health. To this end, a PubMed search with the terms 'gut microbiota, ' 'obesity' and 'insulin sensitivity' was performed. Expert opinion: Many properties of the human gut microbiome are associated with the central regulation of appetite and metabolic status. Some of these relationships are causal and there are positive effects from certain intervention methods. Microbial manipulation may offer a means to prevent or treat obesity and associated co-morbidities. However, to establish direct causal relations between altered gut microbiota and metabolic disease, clinical intervention studies are necessary.